The Mental Health and Wellbeing of EU Citizens in the UK: A Systematic Review of the Qualitative Literature - Teodorowski, Piotr; Woods, Ruth; Kennedy, Catriona (Border Crossing, 2020)
Moving to a new country impacts on migrants’ mental health and wellbeing. There are over 3.6 million European Union citizens living in the United Kingdom. We conducted a systematic review of the qualitative literature to explore what is known about their mental health and wellbeing at the post-migration stage in pre-Brexit period. We searched five databases from 1st January 2009 to 19th February 2019; Web of Science, MEDLINE, CINAHL, SocIndex and Scopus for studies. Ten papers reporting nine studies were included in this review. Two themes were constructed; a narrative of adjustment and of employment realities. The former focuses on the process of settling in and the role of social connectedness. The latter concerns employment realities with included studies exploring the financial position and employment experiences of migrants. Findings indicate that we still know relatively little about the range of post-migration experiences among EU citizens and their implications for mental health